2014
DOI: 10.11120/elss.2014.00019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of How the Blended Use of a Virtual Learning Environment (VLE) Can Impact on Learning and Teaching in a Specific Module

Abstract: This paper explores how the blended use of a Virtual Learning Environment (VLE) can impact on student learning in a specific module within a small university in the UK. Students studying a module about crisis situations faced by children in different parts of the world were asked to contribute to online forums as part of their learning. 47 students participated in the study. Student questionnaires, Moodle reports and student assessment grades were analysed to explore the benefits of online forums. In line with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…The number of student hits on a particular part of a VLE can be viewed as a measure of its success (Lyndon & Hale, 2014), although this is but one indicator and others, such as student perception, are at least as important (Stricker et al, 2011). Nevertheless, 99 postings were made by 72 different students (16% of the cohort), and almost 9,000 views were made in a 17-week period by over 400 different students (93% of the cohort).…”
Section: Discussionmentioning
confidence: 99%
“…The number of student hits on a particular part of a VLE can be viewed as a measure of its success (Lyndon & Hale, 2014), although this is but one indicator and others, such as student perception, are at least as important (Stricker et al, 2011). Nevertheless, 99 postings were made by 72 different students (16% of the cohort), and almost 9,000 views were made in a 17-week period by over 400 different students (93% of the cohort).…”
Section: Discussionmentioning
confidence: 99%
“…A study on "Evaluating students experiences using VLE: Satisfaction and preference in Middlesex University, England"revealed that students' preferred lecture capture and key concepts videos because of their benefits on learning, whereas lecture capture with PowerPoint slides and audio only were not preferred considering its lesser benefits (Hamutoglu et al, 2019). Lyndon and Hale (2014) highlighted the importance of using VLE for students' engagement with the potential to enhance higher learning skills through the use of interactive online activities such as discussion forums. The study recommended to empower the university teachers to use other VLE interactive tools to promote participation and engagement among students (Molotsi, 2020).…”
Section: Effectiveness Of Virtual Learning Environment (Vle)mentioning
confidence: 99%
“…S35 said, "If we are taught to use every available feature in that platform it would be very easy for us to learn". Many researchers found that more training for teachers and students is essential for online TLA(Ahmed &Ikram Khan, 2020; Gold, 2001;Lyndon & Hale, 2014).The interaction of students, teachers and materials will be effective on the VLE platform, if the students are given enough training sessions on using VLE features.…”
Section: Benefits and Challenges Of Using Vle Features For Online Tlamentioning
confidence: 99%
“…Over the last 20 years, the teaching and learning landscape of universities has encountered unprecedented change as institutions adapt to the challenges and innovations of technology (Saykili, 2019). However, institutions appear undecided about how to measure the impact of virtual learning environments (VLEs), usually resorting to measuring success in terms of the number of student hits on a particular online resource (Donnelly and O'Rourke, 2007;Lyndon and Hale, 2014). Due to the current global pandemic crisis, educational institutions were forced to adapt to various teaching-learning activities while establishing a linkage between a change management process and an online teaching process, as to Effect of attendance on student performance overcome any persisting academic disturbance to the procedure in the education system (Mishra et al, 2020).…”
Section: Introductionmentioning
confidence: 99%